PENGOPERASIAN DASAR PEMROGRAMAN WEB HTML UNTUK KALANGAN PEMULA DI SMK HARAPAN BANGSA - Azriel, Azriel Akbar Dinar; Luthfi, M Luthfi Erico C R; Jidan, Muhammad Jidan Hasbialloh; Rafly, Rafly Ramadhan Zaenuri; Ravif, Ravif sujidna; Senna, Shena Belarosya; Inggamer, Yafet (Abdi Jurnal Publikasi, 2024)
This Community Service Program (PKM) aims to provide fundamental knowledge of HTML web programming to 11th-grade students majoring in Computer and Network Engineering (TKJ) at SMK Harapan Bangsa. HTML (Hypertext Markup Language) is the standard markup language used for creating web pages. Developed by Tim Berners-Lee in 1990, HTML enables the development of informative and interactive web content. Through this program, students are introduced to the syntax and use of HTML tags to create accessible and engaging web content. The outcomes of this activity are expected to enhance students' understanding and basic skills in web programming, enabling them to effectively utilize web technology in the digital era.